Handbook of Molecular Electronics and Microelectromechanical Systems - Narvaez, Hillary, author 643754; Phelps, Rylee, author 645286 (Delhi, India : Academic Studio, 2012)
This is a well written Handbook of Molecular Electronics and Microelectromechanical Systems.